Pengembangan Bahan Ajar Ekonomi Berbasis Komputer dengan Model Tutorial Pada Pokok Bahasan Uang dan Perbankan Untuk Siswa Kelas X MA Mu’allimin Nw Pancor - Huzain Jailani; Qurratul Aini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2017)
The purpose of this research and development are: 1) to produce computer-based economic teaching materials with tutorial model that will survive and used for subsequent years in grade X students MA Muallimin NW Pancor 2) to know the feasibility of computer-based economic resources developed in the assessment (3) knowing teacher and student responses to computer-based economic learningmaterials with developed turorial models, and 4) knowing the effectiveness of computer-based economic teaching materials with developed tutorial models. This type of research is a research development with Borg and Gall model that has been modified into eight development steps. Development steps include: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revisions, 6) product trials, 7) product revisions, and 8) final product. Data collection was done by observation, questionnaire and test.The result of the research shows that the computer-based economic teaching material with this tutorial model is feasible to be used, it can be seen from the result of the validation of economic material expert of 85.45% (feasible), for the media expert of 86.66% (feasible). furthermore for teacher and student response show positive response seen from result of field trial that result of questionnaire teacher response sebesari 90% and student response equal to 88,90%. For the result of learning activity of student equal to 3,7 and from result of classical student learning completeness show 90,32%, thus computer-based economic resource with this tutorial model effective use. Based on the results of this study is expected for teachers to be able to apply and use this learning materials in the learning process so that students can learn easily and more fun